Transdisciplinary approaches to target product profile (product concept) design: NARES-IRRI partnerships in Africa - Mangwana, Kennedy; Dixit, Shalabh; Menge, Daniel; Panchbhai, Ajay (International Rice Research Institute, 2024)
Rice is becoming an increasingly important food and commercial crop in many African countries, driven by shifts in dietary habits and population growth. In 2023, Africa’s self-sufficiency stood at around 60%, leading to substantial imports to meet the growing demand. To maximize return on investment in research and the deployment of new climate-resilient varieties, key target market segments, their sizes, and impact possibilities have been identified for East and Southern Africa (ESA) where four key market segments have been mapped i.e. TMeLS-R, TMeLS-I, TMeLS-I (salinity) and DELS-R.